The administrative process and decision-making in three-star hotels (Gestionar: revista de empresa y gobierno, 2023)
This study investigates the decision-making process and administrative management of three-star hotels in Acapulco, Mexico, specifically in the Nautical Zone. The main objective was to understand how managers of these hotels apply elements from different phases of the administrative process. The approach was qualitative, using grounded theory, and interviews were conducted with six hotel managers selected through a non-probabilistic convenience sampling method. In general, it was observed that the management of these establishments is carried out empirically, characterized by centralized decision-making in the manager or owner, resulting in a notable concentration of authority. As a result of the research, a model of administrative management is proposed with the aim of optimizing these practices and promoting the business development of three-star hotels.
Keywords: management; hotels; administrative process; decision-making